Analisis Peran Ekonomi Kreatif Dalam Peningkatan Pendapatan Pengrajin Ditinjau Dari Ekonomi Islam (Studi Pada Industri Bordir Kecamatan Indrajaya Kabupaten Pidie) - Murni, Seri; R, Rekha (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
This study aims to reveal the role of the creative economy in increasing the income of embroidery craftsmen in Indrajaya District, Pidie Regency. This thesis uses a descriptive qualitative approach with data collection methods through observation, interviews and documentation. The results of the study illustrate that the creative economy of the embroidery industry in Indrajaya sub-district, Pidie Regency is already good, it can be seen from 15 craftsmen found that 9 craftsmen experienced an increase in income, 6 craftsmen with stable income from 2019 to 2020. While in the Islamic economic perspective, the craftsmen have fulfilled the production process , marketing markets, government policies, economic conditions and partnerships, but have not met the management and financial indicators.